4-Acetylpyridine–fumaric acid (2/1) - Xu, Kan (International Union of Crystallography, 2009)
In the crystal structure of the title cocrystal, 2C(7)H(7)NO·C(4)H(4)O(4), the complete fumaric acid molecule is generated by a crystallographic inversion centre. The two components of the cocrystal are linked by an O—H⋯N hydrogen bond.